Hilda Hellwigs vilda kvinnor - Rosenberg , Tiina (Tidskrift för genusvetenskap, 1997)
From the very first preformance Ta de lugnt, Morsan / C a lm Down, M o t h e r / f r om 1979 to the last, Indras Dotter / T h e Daughter of I n d r a / f r om 1994 Teater Aurora's productions have demonstrated an unusual awareness of gender and gender issues. This article takes a closer look at Hilda Hellwig, Teater Aurora's artistic leader, and her productions focusing o n contemporary women.